Some Physiological Responses of Native Sheep Breeds to Environmental Conditions during Grazing in Natura 2000 Habitats - Monika Greguła-Kania; Paulina Nazar; Mariusz Kulik; Krzysztof Patkowski; Agata Hahaj-Siembida; Andrzej Junkuszew (Agriculture, 2023)
The calcareous xerothermic grasslands of the Festuco-Brometea class are among the most endangered Natura 2000 sites in Europe. The greatest threats include a lack of grazing, secondary succession, and invasive alien and expansive native species. The abandonment of such grasslands is caused by the low nutritional value of biomass, as well as by difficult habitat conditions. The aim of this study was to assess the physiological responses of native sheep breeds to hard environmental conditions when grazing in Natura 2000 habitats and to confirm the hypothesis that native sheep of the Świniarka and Uhruska breeds can be used to protect valuable natural habitats. The analysed grasslands were characterised by very difficult climatic and edaphic conditions and a low fodder value for sheep. Grazing in environmentally valuable areas, sometimes poor in fodder, did not adversely affect the welfare of grazed sheep. In both the Uhruska and Świniarka breeds, there were no indicators for heat or nutritional stress, but physiological changes were observed in the animals’ adaptation to new environmental conditions. Despite poor fodder positions, Świniarka sheep improved their condition and body weight. Fluctuations in indicators showing an adaptation process were also visible.